A love story with Viewpoints: Rehearsing our “self-rehearsing” (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article freely shares experiences of the researcher, who practices and conducts Viewpoints’s training at Studio Oito Nova Dança in São Paulo. Her first contact with Viewpoints was in 1997 at Fall Studio Session, held by SITI Company in New York. She points out, in her approach, the principles, foundations and assumptions of this technique of improvisation, and ventures to understand its importance as an experience for the pedagogy and reflection on the training of the performing artist.
Keywords: Viewpoints; Improvisation; Experience Pedagogy; SITI Company; Mary Overlie.